On An International Level, What Are The Functions Of An Individualized Education Program (IEP) Or Transition Plan (TP)? - Myara, Nathalie (2022)
More than 45 years of IEP/TP research and a few focused on IEP/TP functions or roles. Yet, the quality of an IEP/TP relies on the functions that it fulfills to satisfy the needs of its different users (Petitdemange,1985). The Quebec Ministry of Education (MEQ, 2004) and the Office of Special Education and Rehabilitative Services within the U.S. Department of Education (in Eichler, 1999) explicitly identified and described six to seven IEP/TP functions. However, a literature review and practising environments highlighted a greater number of functions. The goal of this research is to identify the different functions that an IEP/TP should fulfill in regard to the different needs of its diverse users. With the use of pedagogical value analysis method (PVA), results show a synthesis of more than 700 functions organized in an IEP/TP Functional Specification Matrix (FSM). The IEP /TP FSM is useful to create, monitor and evaluate IEP/TPs.